Avaliação clínica após a preservação dos nervos sensitivos intercostobraquial e ramo cutâneo lateral do terceiro nervo intercostal durante a dissecção axiliar por câncer de mama - Monica Duarte Pimentel (2011)
The objective of this study was to evaluate the cutaneous sensitivity in the intercostobrachial nerve (ICBN) dermatome and morbidity after surgery of patients in which the nerve was preserved to associate or not the preservation of the cutaneous lateral branch ofthe third intercostal nerve during the axillary lymph node dissection for breast cancer treatment. We carried out a prospective cohort study of 64 patientsdivided into: Group I (n=37) patients with ICBN preservation and Group II (n=27) patients in which the nerve was preserved associated to cutaneous lateral branch. Cutaneous sensitivity was evaluated one year after surgery using: 1) a modified McGill Pain Questionnaire; 2) clinical examination including brachial perimetry; 3) Semmes-Weinstein monofilaments which allows an objective, qualitative, and quantitative evaluation of peripheral nerve lesions. Our results showed that pain wasreported in 11/37 patients from Group I and in O3/27 patients from Group II (p=0,07). The cutaneous sensitivity was preserved in 23/37 patients from Group I and in 18/27 patients from Group ll (p=0,71). There was no significant difference in the morbidity after surgery (p=0,58) and in the number of lymph nodes dissected between the two groups (p=0,21). Our results were similar among patients of the two groups and showthat is no additional benefit of preserving the cutaneous lateral branch in addition to the intercostobrachial nerve preservation during axillary lymph node dissection.